(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2022)
An agency cost issue in a corporate world is an issue which arises from conflict of interest among management and its stockholders. Audit committee is one of its factors which play a pivotal role to guide and monitor business related matters of firms while following the national and international audit standards. Corporate governance and financial reporting quality are considered as the backbone of any corporation around the world which is readily handled by the corporate governance to resolve the agency cost issues within an organization. This paper covers involvement of audit committee with respect to corporate governance and its development in financial reporting quality to resolve such mediation issues. It ranges from audit committee formations to its importance, composition, significance (as a part of literature review) with audit committee role in corporate governance and its development for quality financial reporting according to international standards. The paper generally focuses audit committee and not any country or firms. This paper is completely based on descriptive study with exploratory research design and utilized secondary data to fulfill the objectives.